The Effects of Two Strategies N.R.E and Forest (picture by1000 word) in Acquisition the physical concepts of second intermediate Grade students and their creative thinking. (Journal of the College of Basic Education, 2022)
The current research aims to identify the effect of strategic N.R.E and Forest in the acquisition of the physical concepts for the students of the second grade intermediate and their creative thinking, The sample was randomly selected from Al sadiq Al Ameen intermediate school for boys belonging to the Directorate General for the education of the second Rusafa.The research sample consisted of 3 groups two of them are experimental groups and the third is control group, The total number of students was 99 students.The first group consisted of (33) students who were taught according to the strategy of N.R.E and the second experimental. (32) students were taught according to Forrest strategy.The control group consisted of (34) students and were taught according to the usual method. ]{ The sample students were equalization in the variables , time age in moths, the previous information in physics for the first grade intermediate, the measure of creative thinking , A set of teaching plans has been prepared , related to the curriculum and the objectives of each lesson for four chapters of the physics book for the second intermediate grade The researcher prepared the test of the acquisition concepts and the research consisted of 45 objectives paragraphs of the type of multiple choice and the research has been achieved with Validity and Reliability, The researcher adopted the measure of creative thinking test Torrance verbal form as it fits with the age at which the research was applied. The test includes: fluency skill, originality skill ,and flexibility. its virtual honesty has been confirmed and its stability factor has been accounted by means of the test material. Pearson correlation factor was( 0.89), The experiment was applied in the second course of the academic year 17-18, after which the test of the acquisition concepts and the scale of creative thinking was applied to the research groups, and the data was collected and analysis using the appropriate statistical means, the results showed, statistically ‏ by statistically significant differences between the average of students of the two experimental groups and the control group students in the achievement and creative thinking variable for the two experimental groups and did not show a statistically significant difference between the students of the experimental groups in the two variables. According to mentioned above, the researcher made a number of recommendation san dproposals.